2023
DOI: 10.1186/s40623-023-01783-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal change in rock-magnetic properties of volcanic ashes ejected during a 1-year eruption event: a case study on the Aso Nakadake 2019–2020 eruption

Abstract: We investigated temporal changes in the rock-magnetic properties of volcanic ash ejected from the Aso Nakadake volcano during a sequence of ash eruptions from 2019 to 2020. For 39 volcanic ash samples, magnetic hysteresis parameters, including saturation magnetization (Ms), saturation remanent magnetization (Mrs), coercivity (Bc), and coercivity of remanence (Bcr), were obtained. Curie temperature (Tc) of the samples was also estimated using thermomagnetic analyses. Titanium-rich and -poor titanomagnetites wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…At higher pressures, Al 2 O 3 and MgO in the melt are preferentially incorporated into crystals (Mollo et al, 2013). This is in line with the findings of Buddington and Lindsley 1964) and Anai et al (2023), who show that, at low temperatures and pressures, titanomagnetite will be richer in Ti.…”
Section: Old Krakatausupporting
confidence: 88%
See 1 more Smart Citation
“…At higher pressures, Al 2 O 3 and MgO in the melt are preferentially incorporated into crystals (Mollo et al, 2013). This is in line with the findings of Buddington and Lindsley 1964) and Anai et al (2023), who show that, at low temperatures and pressures, titanomagnetite will be richer in Ti.…”
Section: Old Krakatausupporting
confidence: 88%
“…Apart from plagioclase and pyroxene, we present mineralogical (including textural) and geochemical data of magnetic minerals. Magnetic minerals are sensitive to magma composition and differentiation, oxidation state, pressure, and temperature (Buddington and Lindsley, 1964;Haggerty, 1991;Lanza and Meloni, 2006;Mollo et al, 2013;Liao et al, 2016;Anai et al, 2023). Therefore, previous researchers have reported that magnetic mineral characteristics, such as abundance, composition, texture, and grain size can reflect magmatic conditions and processes (Mollo et al, 2013;Lerner et al, 2022;Xu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%